Sperm pHertility: male gamete responses to ocean acidification and other stressors - Campbell, Anna Louise (University of Exeter, 2016)
Ocean acidification (OA) together with other anthropogenic perturbations is projected to dramatically alter marine environments over the coming centuries. The vast majority of marine species reproduce by freely spawning sperm directly into the water column, where fertilisation can then either be external or a female can draw sperm into a burrow, brooding chamber or onto her external surface. Hence, sperm are now being released into rapidly changing seawater conditions. In this thesis, I firstly assess what is currently known on the potential for OA and other anthropogenic stressors to influence freely spawned sperm in marine invertebrate taxa. I then present a series of experimental chapters investigating the influence of OA, as a single stressor or in conjunction with a second stressor, copper, on sperm function, physiology and competitive fertilisation performance in a range of invertebrate taxa. My research demonstrates that sperm are vulnerable to the projected changes in seawater carbonate chemistry under OA, with responses observed at all biological levels from sperm physiology, swimming performance, fertilisation ecology and sperm competitiveness. In a multi-stressor experiment on polychaete gametes and larvae, I provide empirical evidence that changes to seawater pH under OA can alter the susceptibility of early life stages including sperm, to the common coastal pollutant copper. Sperm DNA damage increased by 150 % and larval survivorship was reduced by 44 % in combined exposures, than when exposed to copper alone. As a single stressor OA also acted to significantly reduce Arenicola marina sperm swimming speeds and fertilisation success. This work was followed up with a mechanistic investigation of A. marina sperm swimming performance under OA conditions. I found that the length of time between spawning and fertilisation can strongly influence the impact of OA on sperm performance. Key fitness-related aspects of sperm functioning declined after several hours under OA conditions, and these declines could ...